Pengaruh Tingkat Suku Bunga dan Inflasi Terhadap Jumlah Dana Deposito (The Effect of Interest Rates and Inflation on the Amount of Deposit Funds) - Simanullang, Hotnida Ronauli; Natalia, Novia; Gaol, Feby Yosepha Lumban; Tarigan, Almaura Andinna Br.; Nababan, Celvin Fransiskus; Hasugian, Christnova; Siallagan, Hamonangan (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to determine the effect of interest rates and inflation on the amount of deposit funds. This research is quantitative research with data analysis using SPSS. Data was obtained from inflation data and interest rates accessed from the official Bank Indonesia website as well as the monthly financial reports of PT Bank Rakyat Indonesia (Persero) Tbk for the 2016-2020 period which were accessed via the official Bank Rakyat Indonesia website. The research results show that interest rates and inflation have a significant effect on the amount of deposit funds at Bank Rakyat Indonesia during the 2016–2020 period, with a value of 0.000 which is smaller than 0.05. The interest rate partially has a significant impact on the amount of deposit funds at Bank Rakyat Indonesia from 2016 to 2020. This is shown by the regression calculation with a significance value of 0.001, which is lower than 0.05. Meanwhile, partial inflation did not have a significant impact on the amount of deposit funds at Bank Rakyat Indonesia from 2016 to 2020. The research results show a significance value of 0.019, which is higher than 0.05.